Second Order Estimates for Non-Concave Hessian Type Elliptic Equations on Riemannian Manifolds (Journal of Mathematical Study, 2015)
In this paper, we derive second order estimates for a class of non-concaveHessian type elliptic equations on Riemannian manifolds. By applying a new methodfor $C^2$ estimates, we can weaken some conditions, which works for some non-concaveequations. Gradient estimates are also obtained.
Keywords: Non-concave fully nonlinear elliptic equations; Riemannian manifolds; a priori estimates; Dirichlet problem; subsolutions.